Characteristics and complications of diabetes mellitus patients at Royal Prima General Hospital - Audyameca, Nafamoza; Cisca, Anita Merry; Masdalena, Masdalena; Pane, Herlin Novita (Buletin Kedokteran & Kesehatan Prima, 2024)
Diabetes mellitus (DM) is a chronic endocrine disorder characterized by an imbalance in the immune system, with a growing prevalence both globally and in Indonesia. The predominant risk factors for T2DM are sex, age, obesity, smoking, and physical inactivity. Complications of DM can be categorized into microvascular and macrovascular, with higher prevalence rates observed in women and the elderly. This study aimed to describe the characteristics of patients diagnosed with DM at Royal Prima General Hospital in 2023. A quantitative, cross-sectional design was employed, with data collected between May and July 2024. A total of 68 patients were selected using the Slovin formula. The inclusion criteria were patients diagnosed with DM and complete medical records, while the exclusion criteria included incomplete data, deceased patients, or those without complications. Univariate descriptive statistics were used for data analysis. The majority of the 68 patients were aged > 60 years (55.9%) and female (63.2%). The most common occupation was homemaker/unemployed (47.1%), and a significant proportion of the patients had a normal body mass index (86.8%). Microvascular complications were the most prevalent, affecting 54.4% of the patients. Advanced age, female sex, and low physical activity were the dominant factors influencing DM prevalence at Royal Prima General Hospital. Microvascular complications are a major health concern in DM patients.